H12 Huntington's disease and neurodegenerative disorders: a dance between destiny and hope. Forming a community that heals. (12th September 2022) - Alastra, Vincenzo; Invernizzi, Roberta; Ponginebbi, Mariarosa; Camandona, Fabiola; Poenariu, Elena; Fontana, Antonio
Abstract : Background: Huntington's Disease, by its genesis, symptoms and course, threatens to immobilise and isolate entire families in fatigue (including burn-out) and stigma. Aims: The project will structure a narrative space of attention (Care), specific skills for volunteers of multi-channel active listening services, awareness-raising among citizens. Methods: The project orients patients and carers towards a greater social protagonism, favouring the activation of resources complementary to the health/social care to face the destiny of non-self-sufficiency. The current participants (4 patients and 7 carers) were involved in individual and group activities. They were interviewed according to the narrative interview methodology. A non-literal selective transcription was carried out in order to capture the meaning of the testimonies and transfer it to interviewees. Together with the restitution of the text, interviews were carried out on the experience of being interviewed, in that way and on those topics. In groups, the participants began to use expressive skills and preferences to talk about themselves and their experiences, especially in their constructive dimension, ranging from poetic to visual language. Results: The group is being formed, with exchanges and sharing. The interview texts are ready for additions, comparisons and other processing. Conclusions: The project is ongoing. The work with the group will result in further content in different forms of expression (first axis). Training interventions are planned to consolidate and complete specific relational skills in volunteers already active in Telefono Amico Italia (second axis). Citizenship information and awareness-raising interventions will follow (third axis).